De tuinman, de geldschieter, de koelie-werver en de mandoer: Vier portretten van László Székely en de Delische Kunstkring - Pusztai, Gábor (Acta Neerlandica, 2021)
The Hungarian planter László Székely was active as a painter on Sumatra during the first decennia of the 20th century. In 1923 he painted four portraits of people from the planters’ community: The Mandoer, The Moneylender, The Toekang-kebon and The Koelie recruiter, which appeared in the weekly paper De Zweep. In this article I will give an overview of the cultural life in Deli and place Székely’s work in this context. Furthermore, I will explain the uniqueness of Székely’s portraits, using the theory of the English cultural historian Peter Burke.